Traduction et transformation des figures animalières du lion, de l'aurochs et de l'autruche dans le livre de Job - Benabdellah, Matthias Hadi (Semitica, 2024)
This article explores the transformation of the animal figures of the lion, aurochs and ostrich in the Book of Job through various textual traditions. By comparing the Hebrew Masoretic text with Jewish (Targum, Saadia Gaon), Syriac (Peshitta), Greek (Septuagint) and Ge’ez, as well as with two Arabic translations, it highlights the continuities and divergences in the rendering of the animal figures. These adaptations shed light on the process of integrating the biblical text into different cultural contexts.